THE DEADLINE FOR DEPARTURE PREVENTION FROM AN IMMIGRATION LAW PERSPECTIVE - Mulya, Ratna Pristiana; Suparno, Suparno (International Journal of Social Service and Research, 2024)
This study aims to highlight the critical need to update the provisions on departure prevention in Indonesia's Immigration Law, specifically addressing the legal uncertainty arising from the phrase "at any time" in Article 97 Paragraph (1), which has the potential to cause prevention without an exact time limit. The study utilized a qualitative approach, employing a combination of legal analysis and empirical observation. The case approach allowed the author to analyze court decisions or concrete cases related to departure prevention, providing insights into how these regulations were implemented in practice and their implications for individual rights. The analysis focused on the implications of these legal frameworks for individuals' rights and the effectiveness of departure prevention measures, drawing connections between legal norms and their practical outcomes. The research provides a foundation for further discussions on enhancing legal certainty and protecting individual rights within the immigration framework, thereby contributing to the overall improvement of the legal system in Indonesia.